Higher-order contributions and nonperturbative effects in the nondegenerate nonlinear optical absorption of semiconductors using a two-band model - Hannes, Wolf-Rüdiger; Meier, Torsten (Physical Review B)

Potassium titanyl phosphate (KTP) quasiparticle energies and optical response - Neufeld, Sergej; Bocchini, Adriana; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
The KTiOPO4 (KTP) band structure and dielectric function are calculated on various levels of theory starting from density-functional calculations. Within the independent-particle approximation an electronic transport gap of 2.97 eV is obtained that widens to about 5.23 eV when quasiparticle effects are included using the GW approximation. The optical response is shown to be strongly anisotropic due to (i) the slight asymmetry of the TiO6 octahedra in the (001) plane and (ii) their anisotropic distribution along the [001] and [100] directions. In addition, excitonic effects are very important: The solution of the Bethe–Salpeter equation indicates exciton binding energies of the order of 1.5 eV. Calculations that include both quasiparticle and excitonic effects are in good agreement with the measured reflectivity.

Integration von Sprach- und Fachlernen im Kontext chinesisch-deutscher Kooperationsstudiengänge am Beispiel des Maschinenbaustudiums an der Chinesisch-Deutschen Technischen Fakultät (CDTF, Qingdao/Paderborn) - Denzer, Vera; Didier, Andrea; Drumm, Sandra; Hambach, Dennis; Kaplinska-Zajontz, Marta; Noeke, Josef; Settinieri, Julia; Xi, Lin; Zhu, Hongyu (Informationen Deutsch als Fremdsprache)
Am Beispiel des chinesisch-deutschen Kooperationsstudiengangs Maschinenbau an der Chinesisch-Deutschen Technischen Fakultät in Qingdao (China) werden unter Rückgriff auf unterschiedliche im Rahmen formativer Evaluation erhobener Datensätze Möglichkeiten und Grenzen der Integration von Fach- und Sprachlernen sowie Optimierungsmöglichkeiten der Unterstützung des studienvorbereitenden und -begleitenden (Fach-)Spracherwerbs diskutiert.

Ein Beitrag zum stoffschlüssigen Fügen durch plastische Deformation: partielles Kaltpressschweißen durch inkrementelles Walzen - Schmidt, Hans Christian

Ein Beitrag zur Herstellung von hybriden Bauteilen mittels Reibdrücken - Lossen, Benjamin

Beyond Big Data Capitalism, Towards Dialectical Digital Modernity: Reflections on David Chandler’s Chapter - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Introduction: Big Data Capitalism – Politics, Activism, and Theory - Fuchs, Christian; Chandler, David (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Karl Marx in the Age of Big Data Capitalism - Fuchs, Christian (Digital Objects, Digital Subjects: Interdisciplinary Perspectives on Capitalism, Labour and Politics in the Age of Big Data)

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Evidence submitted to the House of Commons-Environment, Food and Rural Affairs Committee’s Inquiry on Rural Broadband and Digital Only Services, published on 26 June 2019 - Fuchs, Christian; Michalis, Maria

Slow Media: How to Renew Debate in the Age of Digital Authoritarianism - Fuchs, Christian (The Conversation)

Henry A. Giroux and the Culture of Neoliberal Fascism - Fuchs, Christian (Los Angeles Review of Books)

Herbert Marcuse: Einige gesellschaftliche Folgen moderner Technologie - Fuchs, Christian (Zeitschrift für Didaktik der Philosophie und Ethik)

Anisotropic Water-Mediated Proton Conductivity in Large Iron(II) Metal–Organic Framework Single Crystals for Proton-Exchange Membrane Fuel Cells - Bunzen, Hana; Javed, Ali; Klawinski, Danielle; Lamp, Anton; Grzywa, Maciej; Kalytta-Mewes, Andreas; Tiemann, Michael; von Nidda, Hans-Albrecht Krug; Wagner, Thorsten; Volkmer, Dirk (ACS Applied Nano Materials)
Herein we present a new proton-conducting iron(II) metal–organic framework (MOF) of an unusual structure formed by chains of alternating bistriazolate-p-benzoquinone anions and iron(II) cations with four axially coordinated water molecules. These chains assemble via π–π stacking between the aromatic units to form a three-dimensional grid-like network with channel pores filled with water molecules. The material was structurally characterized by single-crystal XRD analysis, and its water and thermal stability was investigated. The proton conductivity was studied by impedance measurements on needle-like single crystals. A simple but efficient measurement setup consisting of interdigital electrodes was used. The influence of the crystal orientation, temperature, and humidity was investigated. The iron(II)-MOF showed the highest proton conductivity of 3.3·10–3 S cm–1 at 22 °C and 94% relative humidity. Contrary to most known structures, the conductivity in this material is controlled by chemical properties of the pore system rather than by grain boundaries. The presented material is the starting point for further tailoring the proton-conducting properties, independent of morphological features which could find potential applications as membrane materials in proton-exchange membrane fuel cells.

Copper Oxide/Silica Nanocomposites for Selective and Stable H2S Gas Detection - Paul, Andrej; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten (ACS Applied Nano Materials)
A composite material of copper oxide (CuO) dispersed in the nanopores of KIT-6 silica (SiO2) is used as a dosimetric sensor for the detection of hydrogen sulfide (H2S) gas in low parts per milion concentrations. The sensor principle is based on the reversible chemical conversion of CuO to CuS, which guarantees a high selectivity, and on the corresponding percolation-induced change in electronic conductance.

Sono una madre single. Non sento di poter essere competitiva quanto altri: esperienze di personale precario nelle università del Regno Unito. Translated by Gloria Dagnin - Allmer, Thomas (Studies in Communication Sciences)

Joining of blanks by cold pressure welding: Incremental rolling and strategies for surface activation and heat treatment - Schmidt, H.C.; Homberg, W.; Orive, A.G.; Grundmeier, G.; Duderija, B.; Hordych, I.; Herbst, S.; Nürnberger, F.; Maier, H.J. (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

The Human is Dead, Long Live the Algorithm!. Human-Algorithmic Ensembles and Liberal Subjectivity - Matzner, Tobias (Theory, Culture & Society)
The article analyzes the relation of humans and technology concerning so called ‘intelligent’ or ‘autonomous’ algorithms that are applied in everyday contexts but are far removed from any form of substantial artificial intelligence. In particular, the use of algorithms in surveillance and in architecture is discussed. These examples are structured by a particular combination of continuity and difference between humans and technology. The article provides a detailed analysis of boundary practices that establish continuity and oppositions between humans and information technology, referring to their exemplary depiction in movies. Both strands of boundary practices have the potential to challenge as well as sustain the position of the human as liberal, autonomous subject. Finally, it is shown how the particular combination of continuity and difference that structures the use of algorithms maintains the power of liberal, autonomous subject positions, while the shift of decisions to the algorithms seems to decenter the human.

Privacy - Matzner, Tobias; Ochs, Carsten (Internet Policy Review)

Mediale und soziale Bedingtheit der Subjekte des Privaten – ein Versuch mit Hannah Arendt - Matzner, Tobias (Privatsphäre 4.0. Eine Neuverortung des Privaten im Zeitalter der Digitalisierung)

Organic Self-Adaptable Real-Time Applications - Khaluf, Lial; Rammig, Franz-Josef

History and Aesthetics of Progress Indicators [Edistymispalkkien historia ja estetiikka] - Raczkowski, Felix; Shnayien, Marie-Luise (Tekniikan Waiheita)

Zwei Betrachtungen von Sicherheit und Privatheit nach Snowden - Auerbach, Benedikt; Shnayien, Marie-Luise; Kiltz, Eike; Tuschling, Anna (Datenschutz und Datensicherheit - DuD 43)

Determinant groups of Hermitian lattices over local fields - Kirschmer, Markus (Archiv der Mathematik)
We describe the determinants of the automorphism groups of Hermitian lattices over local fields. Using a result of G. Shimura, this yields an explicit method to compute the special genera in a given genus of Hermitian lattices over a number field.
Keywords: General Mathematics

Jesus-Transformation als Filmmusikkinderbibel. Mario Castelnuovo-Tedescos Klavierzyklus „Εὐαγγέλιον. La storia di Gesù, narrata ai Fanciulli in 28 piccoli pezzi per Piano“ (1949) - Schroeter-Wittke, Harald (Jesus-Transformationen)

Gott lässt sich nicht spotten! (Gal 6,7) Blasphemie als theologisches, strafrechtliches und (religions-)pädagogisches Thema. Eine evangelische Position - Schroeter-Wittke, Harald (Staat und Religion. Aspekte einer sensiblen Verhältnisbestimmung)

Vertrauens-Bildung in evangelische Übergänglichkeit. Eine Einführung in Gemeindekultur- und -medienpädagogik - Schroeter-Wittke, Harald; Fermor, Gotthard (Gemeindepädagogik)

David Danced. Musikalische Spurensuche zu einer populären Szene - Schroeter-Wittke, Harald (Davidfigur und Opfermotiv. Jüdisch-christliche Transformationen)

8. Sonntag nach Trinitatis (11.8.2019). Jes 2,1-5: Auf geht’s – Von Sehnsuchtsliedern und Rückenwind - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Jubilate (3. Sonntag nach Ostern) 12.05.2019. Sprüche 8,22-36: Ein Lustspiel als Grammatik des Lebens - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien I/2)

Kleinkinder und Medien in Deutschland: Eine kultursensible Studie zur (Re-)Konstruktion mediatisierter Kultur- und Sozialisationskontexte in der Frühen Bildung - Günesli, Habib
Dieses Promotionsvorhaben zentriert die Frühe (Medien-)Bildung sowie die Forschungs- und Themengebiete Migration und Interkulturalität, die in der Kindheitsforschung generell und kulturvergleichenden Kindheitsforschung speziell bislang nicht hinreichend berücksichtigt wurden. Der Fokus der vorliegenden Qualifikationsarbeit, die im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang (2010-2012) entstanden ist (vgl. Marci-Boehncke/Rath 2013), liegt daher auf den jenseits quantitativer Nutzungsstudien (vgl. z.B. mpfs 2015; 2013) verhältnismäßig gering beachteten Lebens- und Medienwelten von Vorschulkindern in Abhängigkeit von ihrer familiär praktizierten Herkunftskultur bzw. einer mehrkulturellen (Medien-)Sozialisation. Mit dieser Qualifikationsarbeit wurde das Ziel verfolgt, unter kultursensitiver und intersektionaler Perspektive, in einem multiperspektivischen und multimethodischen Design sowohl empirisch-quantitative als auch empirisch-qualitative Daten zu erfassen und so die (Medien-)Sozialisationskontexte von unterschiedlich (herkunfts-)kulturell geprägten, speziell deutsch-türkischen und deutschen, vier und fünf Jahre alten Kindern, mit Bezug auf die sozialen Felder Familie und Kita, möglichst unverfälscht, also am gemeinten Sinn sozialen Handelns, zu (re-)konstruieren. Ziel ist es, bildungsbiographisch bedingte und als ungünstig verstandene Lebenslagen, Lebensphasen und Lebensweisen möglichst früh zu erkennen und auf diese im Verbund, im Sinne der Educational Governance (vgl. Marci-Boehncke/Rath 2013; Heimbach- Steins/Kruip 2011), zu reagieren, um Kindern in Sachen Bildungs- und Teilhabechancen generell und Mediennutzung und Medienkompetenzvermittlung speziell möglichst günstige „Ausgangsbedingungen zum Schuleintritt [...] zu ermöglichen“ (Marci- Boehncke/Weise 2007, 45) – und zwar über alle sozialen ungleichheitsdimensionellen Prägungen hinweg. Um bestehende Kenntnislücken und Spekulationen, die beim erzieherischen Personal nachweislich bestehen, schließen zu können, sollte ein Zugang zu den gegenwärtig konkreten lebens- und medienweltbezogenen Wirklichkeiten der untersuchten Kinder ermöglicht werden. Entsprechend erfolgte die Konzeption dieses (Teil-)Projekts vor dem Hintergrund der Habitus- und Kapitalsortentheorie von Bourdieu (1987; 1986; 1983). Als Methode der quantitativen Datengewinnung wurden halbstandardisierte Fragebögen gewählt, die den Eltern und Erzieher_innen zu Beginn und mit Abschluss der Projektdurchführung für die Bearbeitung zur Verfügung gestellt und mit Hilfe der Fragebogen-Software GrafStat erfasst und ausgewertet wurden. Das qualitative Datenmaterial, das während der Projektdurchführung mittels der Puppet-Interview- Methode (vgl. Weise 2008; Paus-Hasebrink 2005) gewonnen werden konnte, wurde vor dem Hintergrund der Grounded Theory und mittels der Daten- und Analysesoftware MaxQDA ausgewertet (vgl. Strübing 2011; Glaser/Strauss 2005). Auf der Grundlage der Heuristischen Sozialforschung (vgl. Kleining 1995) wurde auf Methoden- und Datenebene dieses Vorhabens ein komplexes, trianguliertes Forschungsdesign eingesetzt (vgl. Flick 2011).
Keywords: Frühe Kindheit; Frühe Medienbildung; Bildungsgerechtigkeit; Kultursensitivität; Inklusion; Intersektionalität

"iphone Abi" - Erfahrungen eines deutsch-türkisch geprägten Kleinkindes mit Medien im Enkulturationsprozess (Medien: Wissen - Können - Wollen: Medienbildung, Medienkritik, Partizipation, Digitalität, Ethik. Festzeitschrit zu Ehren von Professor Dr. Dr. Matthias Rath)
Habib Güneşli diskutiert in seinem Artikel die Wortschöpfung iPhone Abi, die ein deutsch-türkischer Junge nutzt, um sich sprachlich im multikulturellen Raum zu orientieren.

Experimental Reconstruction of Entanglement Quasiprobabilities - Sperling, Jan; Meyer-Scott, E.; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Letters)

Subcycle Wannier-Stark Localization by Mid-Infrared Bias in Gallium Arsenide - Meier, Torsten; Bühler, Johannes; Schmidt, Christian; Heinrich, Alexander-Cornelius; Allerbeck, Jonas; Podzimski, Reinold; Berghoff, Daniel; Schmidt, Wolf Gero; Reichl, Christian; Wegscheider, Werner; Brida, Daniele; Leitenstorfer, Alfred (XXI International Conference on Ultrafast Phenomena 2018 (UP 2018))
The fundamental interband absorption in gallium arsenide shows a strong blue shift when biased by mid-infrared transients exceeding 10 MV/cm. This subcycle feature is induced by the localization of electronic wavefunctions from 3D to 2D.

Spatially asymmetric transients of propagating exciton-polariton modes in a planar CdZnTe/CdMgTe guiding structure - Vondran, J.; Spitzer, F.; Bayer, M.; Akimov, I. A.; Trautmann, Alexander; Reichelt, Matthias; Meier, Cedrik; Weber, N.; Meier, Torsten; André, R.; Mariette, H. (Physical Review B)

Generating two-mode squeezing with multimode measurement-induced nonlinearity - Riabinin, Matvei; Sharapova, Polina; Bartley, Tim; Meier, Torsten (arXiv:1912.09097)
Measurement-induced nonclassical effects in a two-mode interferometer are investigated theoretically using numerical simulations and analytical results. We demonstrate that for certain parameters measurements within the interferometer lead to the occurrence of two-mode squeezing. The results strongly depend on the detection probability, the phase inside the interferometer, and the choice of the input states. The appropriate parameters for maximized squeezing are obtained. We analyze the influence of losses and confirm that the predicted effects are within reach of current experimental techniques.

Attosecond temporal confinement of interband excitation by intraband motion - Song, Xiaohong; Zuo, Ruixin; Yang, Shidong; Li, Pengcheng; Meier, Torsten; Yang, Weifeng (Optics Express)

Ballistic photocurrents in semiconductor quantum wells caused by the excitation of asymmetric excitons - Duc, Huynh Thanh; Ngo, Cong; Meier, Torsten (Physical Review B)

Oxygen and potassium vacancies in KTP calculated from first principles - Bocchini, Adriana; Neufeld, Sergej; Gerstmann, Uwe; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Improved set up strategies for steel strip straightening machines - Rostek, Tim; Homberg, Werner (AIP Conference Proceedings 2113, 170018)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Bestimmung von Wärmeverlusten in Haushaltskältegeräten - Paul, Andreas; Moczarski, Lukas; Gieselmann, Mirko; Reineke, Michael; Elsner, Andreas; Baumhögger, Elmar; Sonnenrein, Gerrit; Vrabec, Jadran
Wie jedes technische System unterliegen auch Haushaltskältegeräte einer alterungsbedingten Degeneration, die zu einem Anstieg der Energieaufnahme über die Lebensdauer dieser Geräte führt. Ursache hierfür sind verschiedene Effekte, die in dem vom BMWi geförderten Projekt ALGE untersucht werden. Aus den so gewonnenen Erkenntnissen sollen dann degenerationsbeständigere Haushaltskältegeräte entwickelt werden. Eine wichtige Alterungsursache ist der Anstieg der Wärmeleitfähigkeit des PUR-Schaums der Gehäuseisolierung. Zur Bestimmung dieses Einflusses auf die Energieaufnahme ist die Entwicklung neuer Messmethoden notwendig, die zerstörungsfrei sein und den realen Anwendungsbedingungen möglichst nahekommen sollen. Dazu wurde eine Wärmesenke entwickelt, die den Geräteinnenraum unabhängig vom Kältekreislauf abkühlt. Die Wärmesenke ist als Eiswasserbehälter ausgeführt, sodass die Schmelzenthalpie des Eises die durch die Isolierung in den Geräteinnenraum einfallende Wärme aufnimmt. Durch die Bestimmung der Abtauzeit einer bestimmten Eismenge kann so der alterungsbeeinflusste 𝑘∙𝐴-Wert des Gehäuses von Haushaltskältegeräten bestimmt werden.

Loaded Language: Gun Rights and the Rhetoric of Post-Truth Politics. - Jende, Yvonne Kristin (Deception, Dishonesty, and Duplicity, Interdisziplinäre studentische Konferenz)

Qualitätsoptimierung im mechanischen Fügen durch Einsatz von Mensch-Roboter-Kollaboration - Neumann, Stefan; Meschut, Gerson; Schmatz, Frederik; Flügge, Wilko

Surface Inoculation of Aluminium Powders for Additive Manufacturing Guided by Differential Fast Scanning Calorimetry - Tasche, Lennart; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Grundmeier, Guido; Schaper, Mirko; Keßler, Olaf (The Minerals, Metals & Materials Series)

Influence of the process temperature on the tribological behaviour during bulk forming of high nitrogen steel - Kuball, Clara-Maria; Jung, R; Uhe, Benedikt; Meschut, Gerson; Merklein, Marion

Application of Network Analysis to Flow Systems with Alternating Wave Channels: Part A (Pressure Flows). - Schöppner, Volker; Dörner, M.; Marschik, C.; Roland, W.; Miethlinger, J.; Steinbichler, G. (Polymers)

Orientation in LLDPE Cast Films Manufactured under Different Processing Parameters - Bayazian, Hoda; Schöppner, Volker; Yadegari , Ali; Haddad , Hoda

Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Oper und Film. Geschichten einer Beziehung.

Opern für die Leinwand. Erich Wolfgang Korngolds Filmmusik im Hollywood-Melodrama - Ahrens, Stephan (Oper und Film. Geschichten einer Beziehung)

Das Volk lacht auf. Notizen zur DEFA-Komödie - Ahrens, Stephan (Historische Urteilskraft. Magazin des Deutschen Historischen Museums 1)

Julie Delpy: unvermutete Abgründe - Ahrens, Stephan (Filmbulletin, 7)

Ein umstrittener Meister. Nachruf auf den italienischen Opern-, Theater- und Filmregisseur Franco Zeffirelli - Ahrens, Stephan

Geteilte Historische Erfahrung - Ahrens, Stephan (Dschungel (Jungle World))

Die erlösende Kraft des Stars - Ahrens, Stephan (die tageszeitung)

IndieLisboa 2019: Undurchlässige Bilder - Ahrens, Stephan

Biografie Eduard Schreiber - Ahrens, Stephan

Biografie Roland Dressel - Ahrens, Stephan

Biografie Lew Hohmann - Ahrens, Stephan

Biografie Marianne Wünscher - Ahrens, Stephan

Biografie Manfred Krug - Ahrens, Stephan

D2.5 Framework and Sustainability plan for the European CBRN Training Centres network - Schultz, Andreas Maximilian; Di Giovanni, Daniele; Carestia, Mariachiara; Gaudio, Pasquale; Van Heuverswyn, Kathleen; Vybornova, Olga; Cauwenberghs, Bavo; Kiehl, Maximilian; Reich, Wolfgang; Surer, Elif; Pokora, Magdalena; Benson, Elizabeth

D3.8 Report on eNOTICE information and communication platform full operational version (V1) - Schultz, Andreas Maximilian; Kiehl, Maximilian; Marterer, Robin

D3.15 - Links to other CBRN networks and platforms, integration and interface functions on the eNOTICE information and communication platform Report 1 - Schultz, Andreas Maximilian; Marterer, Robin; Dusserre, Gilles; Di Giovanni, Daniele; Van Heuverswyn, Kathleen; Kiehl, Maximilian; Vybornova, Olga; Reich, Wolfgang; Winter, Sarah

D5.5 eNOTICE Progress report 3 - Schultz, Andreas Maximilian; Van Heuverswyn, Kathleen; Vybornova, Olga; Comas, Fra; Raulin, Nicolas; Pratzler-Wanczura, Sylvia; Carestia, Mariachiara; Di Giovanni, Daniele; Kiehl, Maximilian

FFK journal, Heft 4

Guidelines for post processing oriented design of additive manufactured parts for use in topology optimization - Lammers, Stefan; Tominski, Johannes; Zimmer, Detmar (II International Conference on Simulation for Additive Manufacturing Sim-AM 2019 11-13 September, 2019)
According to ISO / ASTM 52900, additive manufacturing (AM) is defined as "the process of joining materials to make parts from 3D model data, usually layer upon layer, as opposed to conventional manufacturing including subtractive manufacturing technologies and formative manufacturing methodologies” [1]. This results in significant advantages over conventional manufacturing methodologies, such as the production of topologically optimized, complex structures, lower material consumption or shorter product development cycles. In order to be able to use these advantages, the possibilities and restrictions of the processes must be known. In particular, selective laser beam melting (SLM), in which a powdery metallic starting material is melted by means of a laser, requires a sound understanding of the process. For this purpose, design guidelines have been presented in various scientific papers. These design guidelines help to design a component in such a way that it can be manufactured successfully using additive manufacturing. These so-called “AMsuitable design guidelines” can be found among others at Adam, Kranz and Thomas [2,3,4,5]. In contrast to established manufacturing processes, the post-processing of additive components is divided into two steps. First, the AM immanent post processing, such as the removing of the component from the building platform or the removing of the remaining powder. These post-processing steps are in the following referred to “post-processing”. Secondly, the subsequent post-processing steps to improve the component properties, such as milling and turning or a stress-relief annealing. These are referred to as “finishing” and form the focus of this paper. With regard to a successful finishing of additively manufactured components, design guidelines must be taken into account that consider the finishing inherent restrictions and possibilities. In the following, these design guidelines are referred to “finishing suitable”. They can deviate significantly from those of conventionally manufactured components in the case of additively manufactured components. Although there are some investigations that deal with the post-processing of additively manufactured components [6,7], there are hardly any design guidelines that are suitable for finishing [8]. Therefore, knowledge about the finishing of additively manufactured components is based on experimental experience rather than on scientific knowledge. For this reason, design guidelines for a finishing suitable design must be methodically determined and quantified. These quantified design guidelines can be used for an automated design check on complex components like topology optimized geometries.

Editorial - Dörre, Robert; Eckel, Julia; Horn, Sarah; Linseisen, Elisa; Zilch, Leonie (FFK Journal, Heft 4)

What does AI see? What does AI know? – An AI Memory Game - Eckel, Julia (Bildbeitrag in: Zeitschrift für Medienwissenschaft Nr. 21 „Künstliche Intelligenzen“ (09/2019))

Fotografische Sozialität. Über Nathan Jurgensons The Social Photo: On Photography and Social Media - Eckel, Julia (Cargo Nr. 43 (09/2019))

Langzeitfestigkeit von Schweißungen aus PP unter Berücksichtigung der Morphologie - Schöppner, Volker; Wübbeke, Andrea; Paul, Andre; Tiemann, Michael; Fitze, F.; Austermeier, Laura; Chen, M.; Jakob, F.; Heim, H.-P.; Wu, T.; Niendorf, T.; Röhricht, M-L.; et al. (Werkstoffwoche (2019))
Langzeitfestigkeit von Schweißungen aus PP unter Berücksichtigung der Morphologie

Forming analysis of tailored tubes with an internal contoured wall thickness and external axial ribs manufactured by internal flow-turning - Wiens, Eugen; Homberg, Werner (PROCEEDINGS OF THE 22ND INTERNATIONAL ESAFORM CONFERENCE ON MATERIAL FORMING: ESAFORM 2019)

Populärkulturelle Automatismen und Sherlock Holmes. Eine Studie in Rot Grün Blau - Adelmann, Ralf (TV-Serie und Literatur. Mosaik einer komplexen Beziehung)

Kulturelle Zyklographie der Dinge

Untersuchung des technischen und pädagogischen Supports an Schulen der Sekundarstufe I in Deutschland – Eine vertiefende Untersuchung zur Studie ‚Schule digital – der Länderindikator 2017‘.Ergebnisbericht der qualitativen Vertiefung mit Perspektiven von Schulleitungen, Schulträgern und Fachdidaktiken - Bos, Wilfried; Lorenz, Ramona; Heldt, Melanie; Eickelmann, Birgit

Computational Thinking Processes and Their Congruence with Problem-Solving and Information Processing - Labusch, Amelie; Eickelmann, Birgit; Vennemann, Mario (Computational Thinking Education)

Computational Thinking and Problem-Solving in the Context of IEA-ICILS 2018 - Eickelmann, Birgit; Labusch, Amelie; Vennemann, Mario (IFIP Advances in Information and Communication Technology)

Computational thinking and problem-solving in the context of IEA-ICILS 2018 - Eickelmann, Birgit; Labusch, Amelie; Vennemann, Mario (Empowering the learner for life in the digital age)

Das Konstrukt der computer- und informationsbezogenen Kompetenzen und das Konstrukt der Kompetenzen im Bereich 'Computational Thinking' in ICILS 2018 - Senkbeil, Martin; Eickelmann, Birgit; Vahrenhold, Jan; Goldhammer, Frank; Gerick, Julia; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern der 8. Jahrgangsstufe in Deutschland im zweiten internationalen Vergleich - Eickelmann, Birgit; Bos, Wilfried; Gerick, Julia; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Nutzung digitaler Medien und Prädiktoren aus der Perspektive der Lehrerinnen und Lehrer im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Schaumburg, Heike; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Der Kompetenzbereich ‚Computational Thinking‘: erste Ergebnisse des Zusatzmoduls für Deutschland im internationalen Vergleich - Eickelmann, Birgit; Vahrenhold, Jan; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Nutzung digitaler Medien aus der Perspektive der Schülerinnen und Schüler im internationalen Vergleich - Schaumburg, Heike; Gerick, Julia; Eickelmann, Birgit; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Schulische Voraussetzungen als Lern- und Lehrbedingungen in den ICILS-2018-Teilnehmerländern - Eickelmann, Birgit; Gerick, Julia; Labusch, Amelie; Vennemann, Mario (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Schulische Prozesse als Lern- und Lehrbedingungen in den ICILS-2018-Teilnehmerländern - Gerick, Julia; Eickelmann, Birgit; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

Die Studie ICILS 2018 im Überblick – Zentrale Ergebnisse und Entwicklungsperspektiven - Eickelmann, Birgit; Bos, Wilfried; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

ICILS 2018 #Deutschland auf einen Blick. Presseinformationen zur Studie und zu zentralen Ergebnissen - Eickelmann, Birgit; Labusch, Amelie

Nutzung digitaler Medien und Prädiktoren aus der Perspektive der Lehrerinnen und Lehrer im internationalen Vergleich - Drossel, Kerstin; Eickelmann, Birgit; Schaumburg, Heike; Labusch, Amelie (ICILS 2018 #Deutschland – Computer- und informationsbezogene Kompetenzen von Schülerinnen und Schülern im zweiten internationalen Vergleich und Kompetenzen im Bereich Computational Thinking)

ICILS 2018 #Nordrhein-Westfalen. Erste Ergebnisse der Studie ICILS 2018 für Nordrhein-Westfalen im internationalen Vergleich - Eickelmann, Birgit; Massek, Corinna; Labusch, Amelie

Digitalisierung im deutschen Bildungssystem im Kontext des Schulreformdiskurses - Eickelmann, Birgit; Drossel, Kerstin (Schulreform – Zugänge, Gegenstände, Trends)

Sortir de la Guerre/Nach dem Krieg: Le Mans & Paderborn 1919-1930

Digitale Räume – Zur Anregung von reflektierter Erfahrung - Herzig, Bardo (Lehrer(in) sein – Lehrer(in) werden – die Profession professionalisieren.)

Bildung in der Digitalität - Herzig, Bardo (bildung + schule digital, Heft 1/2019)

„Lernen ist und bleibt ein sozialer Prozess“. - Herzig, Bardo (ZEIT Online)

Digitalisierung und Mediatisierung: Herausforderungen für die Schule - Herzig, Bardo (Loccumer Pelikan, Religionspädagogisches Magazin für Schule und Gemeinde des Religionspädagogischen Instituts Loccum, Ausgabe 1/2019)

Digitale Medien – bildende Blicke hinter das Interface - Herzig, Bardo (Schule digital – wie geht das? Wie die digitale Revolution uns und die Schule verändert)

Konzeptionelle, strukturelle und inhaltliche Gestaltungsaspekte des Praxissemesters an der Universität Paderborn. - Herzig, Bardo; Wiethoff, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)